Effect of vitamin E and zinc supplementation in pre and post partum period in crossbred cows on anti-oxidant, immunity status and performance of new born calves : Pre and post partum period vitamin E and zinc supplementation effect on performance of new born calves - Sambyal, Madhu Suman; Phondba, Bhupendra T.; Thakur, Devesh; Kaur, Harjit (Indian Journal of Dairy Science, 2023)
The present study was undertaken to study the effect of zinc supplementation alone and its combination with vitamin E on growth, anti oxidant status and immunity status of new born calves of crossbred cows. The cows were supplemented with 0 (T0), Zn @ 80 ppm (T1) and Zn @ 80 ppm + 1000 IU α-tocopheryl acetate/d (T2) from 60 days prepartum up to 90 days postpartum. The fat, SNF, total solid, protein, Zn and Cu contents content of colostrum showing no effect of dietary treatments but α-tocopherol content was higher significantly (P